2023
DOI: 10.1021/acs.analchem.3c01263
|View full text |Cite
|
Sign up to set email alerts
|

Development of a 3D-Printable, Porous, and Chemically Active Material Filled with Silica Particles and its Application to the Fabrication of a Microextraction Device

Abstract: We report on the first successful attempt to produce a silica/polymer composite with retained C18 silica sorptive properties that can be reliably printed using three-dimensional (3D) FDM printing. A 3D printer provides an exceptional tool for producing complex objects in an easy and inexpensive manner and satisfying the current custom demand of research. Fused deposition modeling (FDM) is the most popular 3D-printing technique based on the extrusion of a thermoplastic material. The lack of appropriate material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The result indicated that increasing the silica composition (at a concentration of 10 wt.%) resulted in an increase in tensile strength, ductility and yield strength values, corresponding to the increased mechanical properties of the silica particle-reinforced composite material. A method of preparing a polypropylene/acrylonitrile–butadiene–styrene/C18-functionalized silica composite that can be processed using FDM 3D printing was also described [ 21 ]. The result was an activated, 3D-printed object with a porous structure that allows access to the silica particles while maintaining their macroscopic size and shape.…”
Section: Introductionmentioning
confidence: 99%
“…The result indicated that increasing the silica composition (at a concentration of 10 wt.%) resulted in an increase in tensile strength, ductility and yield strength values, corresponding to the increased mechanical properties of the silica particle-reinforced composite material. A method of preparing a polypropylene/acrylonitrile–butadiene–styrene/C18-functionalized silica composite that can be processed using FDM 3D printing was also described [ 21 ]. The result was an activated, 3D-printed object with a porous structure that allows access to the silica particles while maintaining their macroscopic size and shape.…”
Section: Introductionmentioning
confidence: 99%